The effect of different treatments on improving seed germination and early seedling growth of date palm cv. Medjool - maryam Boroujerdnia; seyed samih marashi; seyyed naser Mousavi (علوم و فناوری بذر ایران)
This study evaluated different methods of improving seed germination in date palm (Phoenix dactylifera L.) of Medjool cultivar. The experiment was laid out in a completely randomized design and each treatment was replicated four times. Treatments were consisting of distilled water for 24 h at ambient temperature, potassium nitrate (KNO3) at 0.5 and 1% for 24 h, sulphuric acid (50% H2SO4) for 3 min, sulphuric acid (98% H2SO4) for 3, 5 and 10 min, boiling water for 5 and 10 min and control(seeds were not treated). The best seed germination and seedling growth were obtained in seed soaking treatments in distilled water and potassium nitrate. The greatest percentage and speed germination was observed in treatment of potassium nitrate (KNO3) at 0.5 % for 24 h. The seeds treated with boiling water for 5 and 10 min and sulphuric acid (98% H2SO4) for 3, 5 and 10 min, did not germinate at all. The lowest Mean time to germination was obtained in distilled water for 24h that had no significant difference with distilled water for 48h, potassium nitrate (0.5 and 1%) for 24h. The highest fresh and dry weight of stem was observed in distilled water for 48 h treatment. The greatest root length was related to control, distilled water (48h) and potassium nitrate (1%) treatments. There was no significant difference between the treatments in shoot height. Therefore, pre-treatment of seeds with distilled water or potassium nitrate effective way to improve seed germination of date palm.